Neuroprotective mechanism of Kai Xin San: upregulation of hippocampal insulin-degrading enzyme protein expression and acceleration of amyloid-beta degradation - Wang, Na (Neural Regen Res, 2017)
Kai Xin San is a Chinese herbal formula composed of Radix Ginseng, Poria, Radix Polygalae and Acorus Tatarinowii Rhizome. It has been used in China for many years for treating amnesia. Kai Xin San ameliorates amyloid-β (Aβ)-induced cognitive dysfunction and is neuroprotective in vivo, but its precise mechanism remains unclear. Expression of insulin-degrading enzyme (IDE), which degrades Aβ, is strongly correlated with cognitive function. Here, we injected rats with exogenous Aβ(42) (200 μM, 5 μL) into the hippocampus and subsequently administered Kai Xin San (0.54 or 1.08 g/kg/d) intragastrically for 21 consecutive days. Hematoxylin-eosin and Nissl staining revealed that Kai Xin San protected neurons against Aβ-induced damage. Furthermore, enzyme-linked immunosorbent assay, western blot and polymerase chain reaction results showed that Kai Xin San decreased Aβ(42) protein levels and increased expression of IDE protein, but not mRNA, in the hippocampus. Our findings reveal that Kai Xin San facilitates hippocampal Aβ degradation and increases IDE expression, which leads, at least in part, to the alleviation of hippocampal neuron injury in rats.